2022
DOI: 10.1155/2022/1455226
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Tendon-Protective Effects of Adipose Stem Cell-Derived Exosomes with Concomitant Use of Glucocorticoids

Abstract: Glucocorticoid (GC) injections are commonly used in clinical practice to relieve pain and improve function in patients with multiple shoulder disabilities but cause detrimental effects on rotator cuff tendons. Adipose stem cell-derived exosomes (ASC-Exos) reportedly recover impaired tendon matrix metabolism by maintaining tissue homeostasis. However, it is unclear whether additional treatment with ASC-Exos overrides the detrimental effects of GCs without interfering with their anti-inflammatory effects. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…After searching the six databases, a total of 1794 studies were found. Forty-five articles were included after screening and all of them were case–control studies [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 86 , 87 , 88 , 89 , 90 ]. Another article was included by searching the references of the included articles and review articles related to the topic [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After searching the six databases, a total of 1794 studies were found. Forty-five articles were included after screening and all of them were case–control studies [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 86 , 87 , 88 , 89 , 90 ]. Another article was included by searching the references of the included articles and review articles related to the topic [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…All studies had a low risk of baseline characteristics under selection bias, random outcome assessment under detection bias, attrition bias, reporting bias, and other biases [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. All studies reported baseline characteristics of the animals used which included the species, age and gender of the animals, and the outcomes were randomly assessed [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations